Professionals' Reported Provision and Recommendation of Psychosocial Interventions for Youth With Autism Spectrum Disorder. Issue 1 (January 2015) - Christon, Lillian M.; Arnold, Cassidy C.; Myers, Barbara J.
Abstract Children and adolescents with autism spectrum disorder (ASD) receive intervention services from multiple professionals across disciplines. Little is known about services for youth with ASD in community settings. The purpose of this study was to provide data on professionals' self-reported practices across different classes of psychosocial interventions for youth with ASD. A multidisciplinary (medicine/nursing, education, occupational/physical therapy, psychology, social work, and speech-language pathology/audiology) sample (N = 709; 86% female; 86% White) of professionals who endorsed providing clinical services to youth with ASD was recruited through convenience sampling (listservs, etc.) and stratified random sampling (online provider listings). Professionals completed a survey on intervention practices with youth with ASD, specifically on their own provision of, as well as their recommendation/referral of, psychosocial interventions (focused intervention practices [FIPs], comprehensive treatment models [CTMs], and other interventions). Hierarchical multiple regression models showed discipline differences in self-reported provision and recommendation of evidence-based FIPs; training variables and unfamiliarity with FIPs predicted rates of providing and recommending. FIPs were reportedly provided and recommended at higher rates than CTMs. Descriptive data are presented on professionals' reported practice of other psychosocial interventions (e.g., cognitive-behavioral therapy). This study highlights the usefulness of examining not only provision of services but also recommendation/referral practices: professionals are important sources of information for families. Implications of the results are discussed in terms of the importance of disseminating intervention information to professionals and the need for consensus on terminology used to classify interventions and on criteria used to evaluate intervention efficacy.